Formation of Academic Papers of Regional Regulations in the Indonesian Constitutional System - Kosariza, Kosariza; Netty, Netty; Yarni, Meri (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Regional regulations (Perda) have a very strategic role in the implementation of regional governance. Various efforts to improve the quality of the Perda continue, including through Law Number 12 of 2011 concerning the Formation of Laws and Regulations which require the preparation of Academic Texts (NA). This study aims to identify and analyze the urgency and implementation of NA drafting in the formation of regional regulations based on legislation. The research method used is normative juridical research, by examining the prevailing norms in the preparation of a guideline in the form of a text with a statutory and historical approach. The results showed that NA has a very important urgency to create a good and quality regional regulation. NA is very important in the process of forming laws and regulations when faced with statutory problems that are considered unresponsive, egalitarian, futuristic, and unqualified. Through NA, each Raperda that gets a scientific touch can produce a higher quality Regional Regulation and can be categorized as good legislation. Given its very vital urgency, it is hoped that the drafters of Perda (Regional Government and DPRD) formulate NA first before compiling the Regional Regulation Draft and provide legal standing for NA compilers in the formation of Perda which need to be regulated in Legislation.